Bridging the divide : working-class culture in a middle-class society - Metzgar, Jack (ILR Press, an imprint of Cornell University Press, 2021)
"An interpretation of the differences between working-class and professional-middle-class cultures in the U.S. since World War II, exploring how these class cultures both conflict with and complement each other"--